A review on chitosan-cellulose blends and nanocellulose reinforced chitosan biocomposites: Properties and their applications. (5th October 2016) - H.P.S, Abdul Khalil; Saurabh, Chaturbhuj K.; A.S., Adnan; Nurul Fazita, M.R.; Syakir, M.I.; Davoudpour, Y.; Rafatullah, M.; Abdullah, C.K.; M. Haafiz, M.K.; Dungani, R.
Highlights: The sources, properties and application of chitosan and cellulose were discussed. The chronological events on chitosan applications were reviewed. Overview on the incorporation of chitosan with nanocellulose were presented. The applications of chitosan-cellulose blends and bionanocomposites were summarized. The potential and challenges of chitosan-cellulose blends were discussed. Abstract: Chitin is one of the most abundant natural polymers in world and it is used for the production of chitosan by deacetylation. Chitosan is antibacterial in nature, non-toxic, and biodegradable thus it can be used for the production of biodegradable film which is a green alternative to commercially available synthetic counterparts. However, their poor mechanical and thermal properties restricted its wide spread applications. Chitosan is highly compatible with other biopolymers thus its blending with cellulose and/or incorporation of nanofiber isolated from cellulose namely cellulose nanofiber and cellulose nanowhiskers are generally useful. Cellulosic fibers in nano scale are attractive reinforcement in chitosan to produce environmental friendly composite films with improved physical properties. Thus chitosan based composites have wide applicability and potential in the field of biomedical, packaging and water treatment. This review summarises properties and preparation procedure of chitosan-cellulose blends and nano size cellulose reinforcement in chitosan bionanocomposites for different applications.